Program evaluation of in-patient treatment units for adults with acquired brain injury and challenging behavior. (23rd February 2022) - Cox, Alison D.; Pontone, Madeline; Gunnarsson, Karl F.
ABSTRACT: Rationale: As acquired brain injury rates continue to increase, the ongoing need for efficient and effective treatment within neurobehavioral rehabilitation settings is clear. Some evidence suggests certain treatment components may be very important to incorporate into service delivery models (e.g., multidisciplinary). However, program evaluation literature and the uptake of complementary intervention strategies, like applied behavior analysis (ABA), in existing neurobehavioral settings remains largely unexplored. Primary Objective: The purpose of this project was to: (1) develop and implement a simple, systematic program evaluation informed by best-practices (i.e., research) to assess service delivery models of several neurobehavioral rehabilitation settings, and (2) survey the current use of ABA by participating neurobehavioral agencies. Methodology: The program evaluation tool was applied to the charts of randomly selected past and current clients (referred to as participants). A secondary research assistant independently reviewed 29% of the charts to conduct interobserver agreement, which s. was 80% (range, 53%-100%) Results: Average program evaluation total percentage score was 33% (range, 4% – 63%), and program evaluation items describing ABA-uptake suggested the incorporation of ABA was low. Discussion: We discuss service model areas of strengths and areas for improvement as specified by tool outcomes, as well as in relation to quality improvement implications.